PENGARUH PERKEMBANGAN PARIWISATA LAGOI TERHADAP EKONOMI MASYARAKAT DI DESA SEBONG PEREH KECAMATAN TELUK SEBONG PROVINSI KEPULAUAN RIAU - Nesti Morita; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was carried out in Sebong Pereh Village, Teluk Sebong District, Riau Islands Province. The purpose of this study was to determine the effect of Lagoi Tourism on the economy of the community in Sebong Pereh Village, Teluk Sebong District, Riau Islands Province. The topic of this research focus is what are the factors of employment opportunities and opportunities that are open to the community in Sebong Pereh Village, Teluk Sebong District, Riau Islands Province. The sampling technique used is Simple Random Sampling. The minimum sample in this study was 98 respondents. The author uses descriptive quantitative methods and data instruments are questionnaires, interviews and documentation. Research conducted, the authors found that the influence of Lagoi Tourism on the economy of the community has three factors influence on society, namely, Labor Effect where Lagoi Tourism presence provides new jobs for people who do not have jobs as many as 91.8% of respondents, Influence of Job Fields where the existence of Lagoi Tourism creates jobs in the manufacture of regional food that is felt as much as 74.5% of respondents, the Effect of Revenue where Lagoi Tourism has an impact on the perceived level of community income as much as 91.8% of respondents. As well as the Influence of Lagoi Social Tourism on the community has four factors of influence, namely the Influence of Social Interaction in which the existence of Lagoi Tourism is friendly to tourists who visit the Lagoi Tourism object which is felt as much as 74.5% of respondents, the Influence of Social Relations where Lagoi Tourism often gives assistance for the development of perceived village facilities and infrastructure as much as 62.2% of respondents, Lifestyle Influence in which the presence of Lagoi Tourism changed the people's lifestyles as much as 18.4% of respondents, consumption pattern influences where since the establishment of Lagoi Tourism the consumption pattern of the people was influenced by trends brought by visitors of Lagoi Tourism. Keywords: Social, Socio-Economic Change, Impact